La falta de tipicidad en las sanciones administrativas impuestas por la superintendencia de compañías, valores y seguros a las fiduciarias por falta de debida diligencia - Barrera Andrade, María Laura (2020)
This thesis aims to demonstrate that the Ecuadorian regulations do not determine with exact and precise criteria the acts or types that constitute the administrative infraction Lack of Due Diligence, and consequently the sanctions imposed on the fiduciaries by the control entity, the Superintendency of Companies, Valores y Seguros (SCVS), are contrary to the constitutional, administrative and sanctioning principles and can generate an excess in the actions of the public official by sanctioning the fiduciaries for one or several acts that may or may not constitute this infraction.